SELF-ESTEEM, ADVERSITY QUOTIENT AND SELF-HANDICAPPING: WHICH ASPECTS ARE CORRELATED WITH ACHIEVEMENT GOALS? - Jumareng, Hasanuddin; Setiawan, Edi (Jurnal Cakrawala Pendidikan, 2021)
Psychology is one of the potential factors to be successful in physical education learning at universities. However, it is still unknown that among self-esteem, adversity quotient, and self-handicapping has more correlation with achievement goals. This quantitative correlational study aims to investigate the correlation among self-esteem, adversity quotient, self-handicapping, and achievement goals. The participants of this study were 80 female students. These student were in the third or fourth years of the participating universities. The instruments to collect the data were self-esteem, adversity quotient, self-handicapping, and achievement goal questionnaires. In statistical analysis, SPSS version 25 was used to find bivariate correlation and regression with a significance level of .05. The results show that self-esteem is positively correlated with adversity quotient, self-handicapping, and goal achievement. Then, the adversity quotient is positively correlated with self-handicapping and achievement goals. Meanwhile, self-handicapping has a negative correlation with achievement goals. To optimally achieve the goals in physical education classes, the aspects of self-esteem and adversity quotient should be correlated. However, self-esteem does not necessarily need to be correlated with self-handicapping. This study benefits the development of science, especially the field of psychology and physical education. The result of this study may be used to produce students with a high level of achievement goals in physical education learning at universities.